An introduction to population geography - Hornby, William Frederic; Jones, Melvyn (Cambridge. New York : Cambridge University Press, 1993)
This text deals with particular themes in human geography and is intended to meet the needs of A-level geography students. It also aims to provide a useful introduction to population geography for students in higher education
Includes bibliographical references and index.
Keywords: Population geography; Population geography -- Case studies